One step electrochemical fabrication of high performance Ni@Fe-doped Ni(oxy)hydroxide anode for practical alkaline water electrolysis. Issue 44 (1st November 2022) - Jiang, Tao; Jiang, Xinge; Hnát, Jaromír; Michalcova, Alena; Biswas, Indro; Reissner, Regine; Kyriakou, Vasileios; Razmjooei, Fatemeh; Liao, Hanlin; Bouzek, Karel; Ansar, Syed-asif
Abstract : Charge-transfer process (CTP) and mass-transfer process (MTP) are essential in water electrolysis. The engineered core@shell nanoarrays-based anode can significantly improve not only CTP but also MTP in AWE cell. Abstract : Oxygen evolution reaction (OER) is a rate-determining process in alkaline water electrolysis (AWE). Herein, we report a novel one-step oxidation–electrodeposition (OSOE) approach to generate core@shell nanoarrays-based AWE electrode with outstanding OER performances: an overpotential of 245 mV at 10 mA cm −2 (Tafel slope: 37 mV dec −1 ), and excellent stability under huge current densities. Moreover, the alkaline (AEL) cell equipped with NM-OSOE-23 anode recorded significant performance improvement of 200 mV lower voltage (2 A cm −1 ) compared with a similar cell used bare Ni mesh as an anode, which was contributed by notable enhancements of interface contact, anodic charge transfer, and mass transfer. These promising results are attributed to the constructed specific core@shell Ni@Fe-doped Ni(oxy)hydroxide nanoarray architecture on commercial nickel mesh. This study demonstrates this first reported OSOE can be commercialized to make highly efficient anodes enabling next-generation AWE.